The effect of nano-silica on the performance of Portland cement mortar - Ammar, Mohamed Mostafa (AUC Knowledge Fountain, 2013)
Nanotechnology has nowadays a pronounced impact on several areas of science and industry. Among several advantages, nanomaterials have been reported to introduce improvements in terms of system reliability, extend functionality beyond traditional applications and decrease energy consumption in structures. Nanomaterials can enable better utilization of natural resources and reaching required materials properties with minimal usage. Nano-cement and nano-silica are among the recently used materials in this regard. The objective of this study is to explore the effect of incorporating nano-silica to cement mortar on enhancing mechanical properties and durability. Three types of nano silica with three nominal particle sizes have been used with two percentages (4% and 8% per weight of cement) and a w/c of 0.4. Testing program included compressive strength, tensile strength, rapid chloride permeability, microstructure analysis, chemical durability and the effect of mixing techniques on strength. The results were compared against both ordinary Portland cement mortar a well as conjugate mortar with 8% of cement silica fume. Results reveal adding nano-silica to cement mortar enhances its physical and mechanical properties such as compressive strength, tensile strength, permeability and chemical durability. The SEM pictures demonstrate that nano-silica contributes to enhancement of mortar through yielding denser, more compact and uniform mixtures. It was also found that nano-silica is superior to silica fume in enhancing the properties of cement mortar although a generalization at that stage needs further examination. The findings of this study should be validated by wider studies and testing scheme. It is recommended that codes of practice should be introduced for testing construction materials with nano-particles.